Penerapan Digital Marketing Pada Layanan E-Commerce Fakultas Teknologi Informasi Universitas Atma Jaya Makassar - Elisabeth; Rangga Agon (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2019)
To anticipate digital industry development in the world that the current is very fast Faculty of Information Technology (FTI) University Atma Jaya Makassar (UAJM) teach the concept of entrepreneur and the concept of online trading (e-commerce) to learners, but in it’s application there are still many shortcomings. This thesis is a container of entrepreneurship development for learners by applying the concept of digital marketing in its development. The author also hopes the E-commerce service system can be a place for academic community and people who ask to market their products, works, or services that they have.